Victims as Offenders : The Paradox of Women's Violence in Relationships - Miller, Susan L. (Book collections on Project MUSE., 2005)
Arrests of women for assault increased more than 40 percent over the past decade, while male arrests for this offense have fallen by about one percent. Some studies report that for the first time ever the rate of reported intimate partner abuse among men and women is nearly equal. Susan L. Miller's timely book explores the important questions raised by these startling statistics. Are women finally closing the gender gap on violence? Or does this phenomenon reflect a backlash shaped by men who batter? How do abusive men use the criminal justice system to increase control over their wives? Do police, courts, and treatment providers support aggressive arrest policies for women? Are these women "victims" or "offenders"? In answering these questions, Miller draws on extensive data from a study of police behavior in the field, interviews with criminal justice professionals and social service providers, and participant observation of female offender programs. She offers a critical analysis of the theoretical assumptions framing the study of violence and provides insight into the often contradictory implications of the mandatory and pro-arrest policies enacted in the 1980's and 1990's. Miller argues that these enforcement strategies, designed to protect women, have often victimized women in different ways. Without sensationalizing, Miller unveils a reality that looks very different from what current statistics on domestic violence imply.